1998
DOI: 10.1111/j.1600-0404.1998.tb07292.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status in acute stroke: undernutrition versus overnutrition in different stroke subtypes

Abstract: In the acute stage of stroke, undernourishment was significantly (P=0.000) more prevalent in the ICH group (62%) than in the CI group (25%) or controls (13%). On the other hand obesity was present in 10%, 24% and 17% in patients with ICH, those with CI, and controls, respectively, which was not significantly different (P=0.461). Only abdominal skinfold thickness was significantly greater in patients with CI than in those with ICH or controls. Conclusions - Our results illustrate that undernourishment is preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 28 publications
2
36
1
5
Order By: Relevance
“…The percentage of patients identified as malnourished, at any point after the stroke, based on the authors' primary criteria, ranged from 6.1% 12 to 62%. 1 If the criteria were widened to include the secondary criteria used in 2 studies, the range of estimates broadened from 1.3% 20 to 73%. 21 Clinical evaluations based entirely on subjective criteria were used in 5 studies.…”
Section: Nutritional Assessmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The percentage of patients identified as malnourished, at any point after the stroke, based on the authors' primary criteria, ranged from 6.1% 12 to 62%. 1 If the criteria were widened to include the secondary criteria used in 2 studies, the range of estimates broadened from 1.3% 20 to 73%. 21 Clinical evaluations based entirely on subjective criteria were used in 5 studies.…”
Section: Nutritional Assessmentsmentioning
confidence: 99%
“…The reference lists of these articles were hand searched and yielded 3 hits. 1,2,10 Two studies were considered duplicates and subsequently excluded. Finestone et al 2 described and reported the nutritional status of the same group of patients in a previously identified publication.…”
Section: Literature Reviewedmentioning
confidence: 99%
See 3 more Smart Citations